2012
DOI: 10.1017/s0373463312000306
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Flexure Effect on Transfer Alignment Performance

Abstract: Transfer Alignment (TA) is the initialisation process of the Inertial Navigation System (INS) of an air-launched weapon before its release by using the data from the aircraft INS. The aim of this paper is to improve the TA performance by taking into account the aircraft flexures deterministically. The developed procedure neither requires captive carry tests for determination of flexures nor increases the size of the problem, and can be used in real-time missions of any type of military aircraft. The procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…Hence, this prediction model provides a promising method to deduce bias error. For example, if the autocorrelation of the dynamic lever arm acceleration and the acceleration of the ship motion, as well as their corresponding cross-correlation coefficient can all be estimated, on the condition that the hydroelastic model, statistical analysis, as well as the finite element are fully analyzed [ 20 ], then the bias error can be calculated and compensated. In future research, we plan to carry out a feasible solution based on this work in order to further enhance the accuracy of TA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, this prediction model provides a promising method to deduce bias error. For example, if the autocorrelation of the dynamic lever arm acceleration and the acceleration of the ship motion, as well as their corresponding cross-correlation coefficient can all be estimated, on the condition that the hydroelastic model, statistical analysis, as well as the finite element are fully analyzed [ 20 ], then the bias error can be calculated and compensated. In future research, we plan to carry out a feasible solution based on this work in order to further enhance the accuracy of TA.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Groves et al [ 16 ] showed that an inherent bias error exists in the attitude-based TA. Other studies [ 17 , 18 , 19 , 20 ] pointed out that this error is related to the correlation between ship angular motion and dynamic flexure. In order to solve this issue, Groves et al [ 16 ] presented a mechanical model where the angular flexures is related to the specific forces and Wu et al [ 21 ] presented a bias error model related to the phase delay between flexure and ship angular motion.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, the randomness of parameters such as lift, drag and moment coefficients incurred by chemical reactions and incomplete knowledge of the temperature distribution in the structure can also be classified as uncertainty. Dynamic errors result from the flexures and vibrations of the aircraft uncertainty structure and become significant especially when the aircraft is maneuvering in the effect of the hypersonic vehicle structural flexural deflections [36]. So TA performance represents the primary challenge in modeling uncertainty.…”
Section: The H1 Sgqkf Application In Transfer Alignmentmentioning
confidence: 99%
“…The model of the dynamic deformation of the aircraft wing can be simulated by the linear function of the specific force of the aircraft. The coefficient matrix of the linear function is closely related to the aircraft’s load, fuel quantity, flight speed and altitude [14]. However, the calculation of the model coefficient matrix is complex, and needs to be continuously updated according to the flight structure and flight state, making the model not compatible.…”
Section: Introductionmentioning
confidence: 99%